AN ANALYSIS OF FIGURATIVE LANGUAGE IN SONG LYRIC ON THE S.I.G.I.T “DETOURN ALBUM” - Elfas Malikhi Ragil Pamungkas; Muhammad Wahyu Widiyanto; Sukma Nur Ardini (Program Studi Pendidikan Bahasa Inggris - Fakultas Keguruan dan Ilmu Pendidikan - Universitas Baturaja, 2022)
This study focused on analyzing the figurative language contained in the album “Detourn”by The S.I.G.I.T as non-native speakers. The aim of this research is; 1) to find out the typeof figurative language used in the album “Detourn” by The S.I.G.I.T. 2) to find out thedominant type of figurative language used in The S.I.G.I.T album “Detourn”. Researchersconducted qualitative research using song lyrics data. The result showed that; 1) there are 8types of figurative language used in the album “Detourn” namely Hyperbole (1), Irony (1),Personification (2), Synecdoche (2), Simile (3), Metonymy (11), Repetition (13), andMetaphor (18). 2) Metaphor is the most dominant type of figurative language with a total of18 expressions. There are 9 songs that have metaphors with an average of 2 expressions ineach song. The first song and the seventh song have 1 expression. The second, third, ninth,tenth and eleventh songs with 2 expressions. The fifth and sixth songs with 3 expressions.